(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The composition of the washing solution consists of surfactant and soda. Under the influence of soda, the residual fat-wax substances in the fiber become soluble, and the surfactant emulsifies the fatwax substances that have passed into this soluble state, ensuring their release from the fiber